A 63-Year-Old Man with Neurofibromatosis Type 1 and Intracerebral Astrocytoma: A Case Report - Wicaksana, Iman Hakim; Geizar Arsika Ramadhana (HM Publisher, 2024)
Background: Neurofibromatosis type 1 (NF-1) is one of the hereditary neurocutaneous disorders. Neurofibromatosis type 1 has broad clinical manifestations that can occur in the skin, bones, eyes, and nervous system. In progressive cases, NF-1 can malign and cause intracerebral tumor lesions. Astrocytoma, especially pilocytic astrocytoma, is one of the tumor classes that patients with NF-1 can develop with far-reaching disease progression. This case report presents a case of NF-1 with intracerebral astrocytoma. Case presentation: A 63-year-old man with whole body lumps since childhood presented with weakness in the right limbs 1 month ago. 3 months earlier, the patient also had a full-body seizure for 1 minute twice. The patient then underwent a magnetic resonance imaging (MRI) examination of the brain and found a mass in the left centrum semiovale, left corona radiata, left insular, left external capsule, and left frontotemporoparietal lobe with a size of 7.2 x 5.3 x 6.2 cm. The patient then underwent a VP shunt followed by tumor resection. The tumor was successfully evacuated, and histopathological examination with hematoxylin & eosin (HE) staining revealed glioblastoma multiformis. The patient also underwent histopathologic examination with Ki-67 immunohistochemistry (IHC) staining and showed pilocytic astrocytoma. Conclusion: Craniotomy of tumor excision is the definitive therapy in neurofibromatosis patients accompanied by intracerebral astrocytoma.